2022
DOI: 10.3389/fendo.2022.876231
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Body Composition, Leptin, and Vitamin D Varied by the Body Fat Percentage in Adolescents

Abstract: BackgroundSerum leptin levels reflects one’s degree of obesity and can affect vitamin D levels. The relationship between body fat, leptin, and 25-hydroxyvitamin D (25(OH)D) has not been extensively studied in adolescents. This study aimed to investigate the correlations between body composition and leptin and 25(OH)D levels in boys and girls.MethodsParticipants aged 12–14 years (n = 205) were grouped according to sex. After body composition was recorded using bioelectrical impedance analysis, they were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…In this work, plasma ghrelin in the fasting state and obestatin levels were measured in obese children and compared with control. In agreement with other past studies in adults 25 and children 26 , this study found that the fasting plasma obestatin levels in obese children increased while ghrelin was lower than the control group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this work, plasma ghrelin in the fasting state and obestatin levels were measured in obese children and compared with control. In agreement with other past studies in adults 25 and children 26 , this study found that the fasting plasma obestatin levels in obese children increased while ghrelin was lower than the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Decreasing levels of ghrelin diminishes its protective role as an antioxidant in obese subjects. Obestatin levels were measured in this study in fasting state in obese children as well as in control and the finding was high levels of fasting plasma obestatin concentrations in obese patients compared with controls, which agrees with former studies in adults 25 . Also, we noticed a positive correlation in a significant way between BMI and obestatin.…”
Section: Discussionsupporting
confidence: 92%
“…A longitudinal study involving African Americans revealed a distinct, independent association between heightened hip circumference, expanded waist circumference, and elevated serum leptin levels ( 52 ). Moreover, a recent study in young adults aged 20 to 21 demonstrated a positive correlation between serum leptin levels, waist circumference, and body fat percentage in both men and women ( 53 ). Furthermore, a study investigating the potential relationship between trunk fat levels and breast gene expression revealed that increased trunk fat levels were correlated with higher levels of leptin ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such variation in the influence of BMI on academic performance may indicate a lower reliability of BMI in assessing total body fat [46]. In addition, some studies have shown a reciprocal association between leptin and 25(OH)D levels among adolescents [47]. Moreover, high levels of leptin are associated with poorer academic performance [48].…”
Section: Discussionmentioning
confidence: 99%